2022
DOI: 10.3390/ijerph192316147
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Recent Suicidal Ideation and Recent, State, Trait and Musical Anhedonias in Depression

Abstract: The aim of the study was to explore in depression the relationship between recent suicidal ideation and the different anhedonias taking into account the severity of depression. Recent studies have suggested that recent change of anhedonia and not state or trait anhedonia is associated with recent suicidal ideations even when the level of depression is controlled. Three samples were used (74 severe major depressives, 43 outpatients with somatic disorders presenting mild or moderate depression and 36 mild or mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Table 1 presents the inclusion and exclusion criteria applied for the recruitment of these major depressed subjects. In addition, in this study, we only recruited major depressed subjects since the objective was to focus on this particular subpopulation where anhedonia complaints seem to play a central role in the occurrence of suicidal ideations [13][14][15]19]. Finally, Annex S1 (Supplementary Data) describes the outpatient recruitment procedure for the major depressed subjects included in this study.…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the inclusion and exclusion criteria applied for the recruitment of these major depressed subjects. In addition, in this study, we only recruited major depressed subjects since the objective was to focus on this particular subpopulation where anhedonia complaints seem to play a central role in the occurrence of suicidal ideations [13][14][15]19]. Finally, Annex S1 (Supplementary Data) describes the outpatient recruitment procedure for the major depressed subjects included in this study.…”
Section: Populationmentioning
confidence: 99%
“…However, despite the fact that anhedonia is a cardinal symptom of major depressive disorder [12], few studies have investigated the role played by this depressive symptom in the occurrence of suicidal ideations in major depressed subjects [13][14][15]. Moreover, unlike other specific subpopulations [16][17][18], the potential impact of the temporal dynamics of anhedonia (lifelong anhedonia and recent changes in anhedonia) on the risk of suicidal ideations has been few studied in major depressed subjects [19], which could limit the interpretation of most of the studies available in the literature. Thus, given these limited data, it seems necessary to carry out additional investigations to better understand the potential role played by the temporal dynamics of anhedonia (lifelong anhedonia and recent changes in anhedonia) in the occurrence of suicidal ideations in major depressed subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Schrader (1997) [42] have shown significant correlations between general anhedonia and a risk of depression. Hein et al (2022) [43], further explored "the relationship between recent suicidal ideation and the different anhedonias", including musical. Indeed, based on previous works, it could be hypothesized that the inability to enjoy music anymore might be a marker of depression.…”
Section: Plos Onementioning
confidence: 99%
“…Self-reported anhedonia is a reliable predictor of a worse long-term course of MDD across several prospective studies ( Morris et al, 2009 ). Notably, some studies suggested that state anhedonia in MDD represents a substantial predictor for suicide ideation (SI) ( Hein et al, 2022 , Hawes et al, 2018 , Loas et al, 2019 ). Anhedonia, as the psychological pain, is a fundamental factor associated with suicide risk concerning short-term fluctuations in SI ( Yang et al, 2020 , Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%